PERENCANAAN STRATEGIS WARD PEPPARD WITH PESTLE - Amanda Agustina; Tiawan; Dedih; Ahmad Mubarok; Lila Setiyani; Asep Obay Badillah; Mutia Nur Anisya; Riaz Citra Hardiman; Rizka Adinda Nurkhoridah (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Strategic planning is the first step in determining the right strategy in an organization. In this case study there are problems related to mapping the direction of technology used by the campus, mapped using the Value Chain and also PESTLE (Political, Economic, Social, Technological, Legal, and Environmental). The Value Chain itself is a value chain consisting of Primary Activities and Secondary/Supporting Activities which has the aim of achieving the vision and mission of the organization, while PESTLE is a tool for knowing all forms of interrelationships from political, economic, social, technological, legal and environmental aspects. The framework used in this strategic planning is the Ward Peppard framework, where these tools and frameworks are expected to help in mapping strategic steps for the organization to grow and develop. Where the mapping aims to assist in long-term strategic planning regarding development blueprints from the IS/IT side of the organization.